Phosphorescent iridium (III) complex with covalent organic frameworks as scaffolds for highly selective and sensitive detection of homocysteine - Deng, Chuti; Xu, Juntong; Zhang, Qi; Fan, Yong (Frontiers in Chemistry, 2024)
Introduction: Developing a convenient and cost-effective platform for detecting homocysteine (Hcy) is of great interest as Hcy has been found to be a biomarker for Alzheimer’s disease, gastric cancer, and other diseases. Methods: In this study, we synthesized five phosphorescent Ir(C∧N)2(N∧N)+ compounds (Irn, n = 1–5) with various substituents (-CHO or -CHO/-NH2), which were then doped into a covalent organic framework (COF) host via covalent bonding. Results and Discussion: The resulting optimal composites (denoted as Ir4/5@EBCOF) with -CHO/-NH2 substituents not only overcame the self-quenching issue of the bare Ir4/5 complexes but also showed rapid, highly selective, and sensitive detection of Hcy, with a limit of detection (LOD) of 0.23 μM and reaction time of 88 s. The sensing mechanism was revealed as the unique cyclization reaction between Ir(III) and Hcy that forms a six-membered ring. During the process, the color changes in the composites can be observed visually. It is expected that these phosphorescent Iridium (III) complexes with COFs will have the potential to serve as promising platforms for detecting thiols.